Structural Characterization of Silica Particles Extracted from Grass Stenotaphrum secundatum: Biotransformation via Annelids - A. Espíndola-Gonzalez; R. Fuentes-Ramirez; A. L. Martínez-Hernández; V. M. Castaño; C. Velasco-Santos (Advances in Materials Science and Engineering)
This study shows the structural characterization of silica particles extracted from Stenotaphrum secundatum (St. Augustine) grass using an annelid-based biotransformation process. This bioprocess starts when St. Augustine grass is turned into humus by vermicompost, and then goes through calcination and acid treatment to obtain silica particles. To determine the effect of the bioprocess, silica particles without biotransformation were extracted directly from the sample of grass. The characterization of the silica particles was performed using Infrared (FTIR) and Raman spectroscopy, Transmission Electron Microscopy (TEM), X-ray Diffraction (XRD), Dynamic Light Scattering (DLS), and Energy Dispersion Spectroscopy (EDS). Both types of particles showed differences in morphology and size. The particles without biotransformation were essentially amorphous while those obtained via annelids showed specific crystalline phases. The biological relationship between the metabolisms of worms and microorganisms and the organic-mineral matter causes changes to the particles' properties. The results of this study are important because they will allow synthesis of silica in cheaper and more ecofriendly ways.